Wait for signs [large type] : twelve Longmire stories - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery., 2015)
"Twelve Longmire short stories available for the first time in a single volume-featuring an introduction by Lou Diamond Phillips of A & E's Longmire. Ten years ago, Craig Johnson wrote his first short story, the Hillerman Award-winning "Old Indian Trick." This was one of the earliest appearances of the sheriff who would go on to star in Johnson's bestselling, award-winning novels and the A & E hit series Longmire. Each Christmas Eve thereafter, fans rejoiced when Johnson sent out a new short story featuring an episode in Walt's life that doesn't appear in the novels; over the years, many have asked why they can't buy the stories in book form. Wait for Signs collects those beloved stories-and one entirely new story, "Petunia, Bandit Queen of the Bighorns"--For the very first time in a single volume. With glimpses of Walt's past from the incident in "Ministerial Aide," when the sheriff is mistaken for a deity, to the hilarious "Messenger," where the majority of the action takes place in a Port-A-Potty, Wait for Signs is a necessary addition to any Longmire fan's shelf and a wonderful way to introduce new readers to the fictional world of Absaroka County, Wyoming"--Provided by publisher.